Perlindungan Konsumen Korban Transaksi Pay Later Traveloka (Contoh Kasus Trias Dian Lestari) - Mulyadi Mulyadi; Gunawan Djajaputra (Syntax Literate, 2023)
Economic development as part of the concept of national development, as an effort to realize the welfare of the people who are just and prosperous. In order to strengthen national development, the government invites the banking world to participate in collecting and distributing public funds, both on a small and large scale. The government issued basic rules of banking law, namely Law Number 10 of 1998 concerning Banking (which was later shortened to the Banking Law). The aim is to regulate various banking activities, both transactions, depositing money, investment and credit so that the public also gets legal protection. Implementation of financial business services to connect lenders with loan recipients to reach loan agreements in rupiah directly through digital platforms using internet services. PayLater is a technology-based lending and borrowing service with the motto "buy first, pay later". Consumers are often considered to have an unequal position with business actors. Consumers are powerless in the face of a stronger position from business actors. This is not in line with the regulations in Law Number 8 of 1999 concerning Consumer Protection (later abbreviated as UUPK), especially Article 4 concerning consumer rights, including the right to comfort, security and safety in consuming goods and / or services received in accordance with the agreement or not as it should be. Based on this reason, the title of this study was raised, namely "Consumer Protection of Traveloka PayLater Transaction Victims (Example: Trias Dian Lestari Case)"